PENGARUH KEMATANGAN GURU, LINGKUNGAN KERJA DAN KEPEMIMPINAN KEPALA MADRASAH TERHADAP KINERJA GURU PADA MADRASAH ALIYAH NEGERI KABUPATEN BATU BARA - Syahri Mauliddin; Khairunnisya .; Muhammad Sya’i; M. Syafi’i; Ayu Roza Fiitri (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2020)
Problem of this study is how influence of   teacher’s maturity on  teacher’s performance. How influence of job environment on  teacher’s performance. How influence of head leadership of madrasah on teacher’s performance. How influence  teacher’s maturity, job environment and   head leadership of madrasah on  teacher’s performance. The purpose of this study to determine and analyze the effect of teacher’s maturity on  teacher’s performance. Determine and analyze the effect of job environment on  teacher’s performance. Determine and analyze the effect of   head leadership of madrasah on  teacher’s performance. Determine and analyze the effect of teacher’s maturity, job environment and   head leadership of madrasah on  teacher’s performance. Sample in the study is 52 teacher’s . Data analysis techniques used in this study is descriptive analyze and multiple linear regression analysis.  The results of the study indicate teacher’s maturity variable has a positive and significant effect on  teacher’s performance.  Teacher’s job environment variable has a positive and significant effect on  teacher’s performance.   Head leadership of madrasah variable has a positive and significant effect on  teacher’s performance.   The teacher’s maturity, job environment and head leadership of madrasah variable has a positive and significant effect on  teacher’s performance.